Semi-Simple Extension of the (Super) Poincaré Algebra - Dmitrij V. Soroka; Vyacheslav A. Soroka (Advances in High Energy Physics)
A semi-simple tensor extension of the Poincaré algebra is proposed for the arbitrary dimensions D. It is established that this extension is a direct sum of the D-dimensional Lorentz algebra so(D−1, 1) and D-dimensional anti-de Sitter (AdS) algebra so(D−1, 2). A supersymmetric also semi-simple generalization of this extension is constructed in the D=4 dimensions. It is shown that this generalization is a direct sum of the 4-dimensional Lorentz algebra so(3, 1) and orthosymplectic algebra osp(1, 4) (super-AdS algebra).